Development of a Sovereign End-to-End Supply Chain for Alpha-Emitter Production to Support Global Targeted Alpha Therapy in Australia and the Pacific. - Melville, Graeme Patrick (Journal of Medical Imaging & Radiation Sciences)
Targeted Alpha Therapy (TAT) using actinium-225 and its short-lived daughter isotopes is emerging as one of the most powerful modalities for treating metastatic and refractory cancers. However, worldwide supply of actinium-225 remains critically limited (<5 Ci annually), constraining clinical access and large-scale trials. This project aims to establish a sovereign, fully integrated alpha-emitter production pipeline to address this global shortfall by utilising indigenous uranium resources and advanced process engineering. To develop and demonstrate an end-to-end process for the safe, efficient, and scalable production of high-purity actinium-225 suitable for clinical use. Specific objectives include: 1. Extraction and purification of radium-226 from uranium-bearing ore. Ore and mineral tailings are processed through a continuous-flow solvent-extraction and phase-separation platform, enabling controlled multistage purification of radium isotopes. Downstream chemical conversion will analytically verify RaCl₂ of radiopharmaceutical purity. Accelerator-based irradiation studies simulate photonuclear transmutation of Ra-226 → Ac225 under varied energy and current regimes. Collaboration with hospital radiopharmacy units ensures alignment with clinical and regulatory standards. All activities are conducted in accordance with radiation-safety and environmental-protection regulations. Theoretical modelling and process design have established the technical feasibility of modern continuous-flow radium separation technology and photonuclear actinium generation. Simulations predict selective recovery of Ra-226 with decontamination factors exceeding 10⁵ and chemical yields above 95%, consistent with radiochemical separation principles. Irradiation modelling under realistic beam-current and energy conditions indicates that actinium-225 yields achievable at pilot scale would be sufficient to meet regional clinical demand. System integration studies confirm that the proposed modular design will minimise waste, enhance operator safety, and enable automation. Laboratory validation of these predictions is scheduled to commence prior to the conference. This project is on-going but demonstrates the technical feasibility and strategic value of a sovereign alpha-emitter production capability in Australia. Establishing a sustainable domestic supply of Ra-226 and Ac-225 will enhance global access to TAT, reduce dependence on legacy reactor-based sources, and position Australia as a regional hub for advanced radiotherapeutics. Supported by national and institutional research initiatives under the Medical Research Future Fund and other governmental science and health programs.